2022
DOI: 10.1017/s0022215121004321
|View full text |Cite
|
Sign up to set email alerts
|

Management of retraction pockets: historic and novel approaches

Abstract: Background Retraction pockets are collapsed segments of the tympanic membrane. Their formation is associated with a disruption in middle-ear ventilation pathways, leading to the loss of organised collagen of the tympanic membrane. There are several approaches in treating retraction pockets, which aim either to improve ventilation or repair the retraction pockets themselves. Methods A review of the literature regarding the classification and associated management of retraction pockets was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
(113 reference statements)
0
2
0
Order By: Relevance
“…Cassano and Cassano 23 utilized the Sadé classification system and Kasbekar et al 27 used the Charachon classification, while the remaining authors did not separate different classifications or did not report classifications at all. Studies have found these staging systems to be poor indicators of management strategy 50,51 with low intra- and inter-rater reliability. 52,53 While the use of a single classification system would be ideal to promote uniformity of assessment, development of a more reliable system is needed before enacting such a change.…”
Section: Discussionmentioning
confidence: 99%
“…Cassano and Cassano 23 utilized the Sadé classification system and Kasbekar et al 27 used the Charachon classification, while the remaining authors did not separate different classifications or did not report classifications at all. Studies have found these staging systems to be poor indicators of management strategy 50,51 with low intra- and inter-rater reliability. 52,53 While the use of a single classification system would be ideal to promote uniformity of assessment, development of a more reliable system is needed before enacting such a change.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of the TM is important for normal hearing. Many diseases cause hearing loss by altering the TM, such as perforations [3][4][5][6][7], retraction pockets [8][9][10][11], and cholesteatoma [11][12][13]. Other ear diseases cause hearing loss by affecting the middle ear space, which lies directly behind the TM, such as ear infections, middle ear fluid, or tumors of the middle ear.…”
Section: Introductionmentioning
confidence: 99%